Role of heat and mechanical treatments in the fabrication of superconducting Ba0.6K0.4Fe2As2ex situ powder-in-tube tapes. (11th August 2015) - Malagoli, A; Wiesenmayer, E; Marchner, S; Johrendt, D; Genovese, A; Putti, M
Abstract: Among the recently discovered Fe-based superconducting compounds, the (K, Ba)Fe2 As2 phase is attracting great attention within the scientific community interested in conductor developments. In fact, after some years of development, critical current densities J c of about 10 5 A cm −2 at fields up to more than 10 T have been obtained in powder-in-tube (PIT) processed wires and tapes. Here we explore the crucial points in the wire/tape fabrication by means of the ex situ PIT method. We focus on scaling-up processes, which are crucial for industrial fabrication. We analyzed the effects on the microstructure of the different heat and mechanical treatments. By an extensive microstructural analysis correlated with the transport properties, we addressed the issues concerning the phase purity, internal porosity, and crack formation in the superconducting core region. Our best conductors, with a filling factor of about 30% heat-treated at 800 °C, exhibited T c = 38 K, the highest value measured in this kind of superconducting tape. The microstructure analysis shows clean and well-connected grain boundaries but rather poor density: the measured J c of about 3 · 10 4 A cm −2 in the self field is suppressed by less than a factor of seven at 7 T. Such not-yet-optimized J c values can be accounted for by the reduced density, while the moderate in-field suppression and a rather high n -factor confirm the high homogeneity and uniformity of these tapes.